ESL pre-university learners' writing apprehension levels in argumentative writing - Jagabalan, J. D. Kumuthini; Tan, Helen; Hossein, Vahid Nimehchisalem (Secholian Publication, 2016)
Writing ability is essential in second language (L2) learners’ educational and professional life. However, experiencing writing apprehension can inhibit the L2 learners’ confidence (Daly, 1975). The objective of this study was to investigate the writing apprehension levels of ESL pre-university learners in writing argumentative composition. 320 pre-university learners from a local institution participated in the study. Two instruments were employed in the study. The first was the Second Language Writing Anxiety Inventory (SLWAI) and the other one was the Analytic Scale of Argumentative Writing (ASAW). The findings revealed a moderate level of writing apprehension among the pre-university learners in argumentative writing. Among the three Second Language Writing Apprehension (SLWA) dimensions, avoidance behaviour obtained the highest mean score. As writing is one of the important components tested in Malaysian University English Test (MUET), the findings of the present study may become a platform for instructors to develop a better understanding about SLWA. Hence, it may throw light on what educators can do to help these L2 learners cope with or eliminate writing apprehension as it hampers the writing quality.